Diagnosis and treatment of bronchiolitis in Finnish and Swedish children's hospitals. (19th May 2014) - Mecklin, Minna; Hesselmar, Bill; Qvist, Erik; Wennergren, Göran; Korppi, Matti
Abstract Aim There is no widely accepted consensus on the diagnosis and treatment of bronchiolitis. This study describes current practices in Finnish and Swedish hospitals. Methods A questionnaire on the diagnosis and treatment of bronchiolitis in children below 2 years of age was sent to all Finnish and Swedish hospitals providing inpatient care for children. All 22 Finnish hospitals answered, covering 100% of the <12‐month‐old population and 21 of the 37 Swedish hospitals responded, covering 74%. Results The mean upper age limit for bronchiolitis was 12.7 months in Finnish hospitals and 12.5 months in Swedish hospitals. In both, laboured breathing, chest retractions and fine crackles were highlighted as the main clinical findings, followed by prolonged expiration. The mean value for the lowest acceptable saturation in room air was 94% in Finnish hospitals and 93% in Swedish hospitals. The most important factors influencing hospitalisation were young age, desaturation and inability to take oral fluids. Finnish doctors preferred intravenous routes, and Swedish doctors preferred nasogastric tubes for supplementary feeding. The first‐line drug therapy was inhaled racemic adrenaline in Finland and inhaled levo‐adrenaline in Sweden. Conclusion The diagnosis and treatment of bronchiolitis is fairly similar in Finnish and Swedish hospitals.